2010
DOI: 10.1530/eje-10-0718
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor gene haplotypes are not associated with birth anthropometry, blood pressure, glucose and insulin concentrations, and body composition in subjects born small for gestational age

Abstract: Objective: Smaller size at birth has been associated with an increased risk of metabolic and cardiovascular disorders in adult life. Fetal programing of the hypothalamic-pituitary-adrenal axis has been suggested as a possible explanation. Fetal glucocorticoid (GC) overexposure has effects that suggest a role of GCs in this programing. The effects of GCs are mediated through the GC receptor (GR or NR3C1). Several functional polymorphisms have been described, which are associated with relative GC resistance or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…In our cohort, we detected an association between N363S and blood pressure; however, it disappeared in the pure carrier analysis after excluding any compound heterozygotes and carriers of BclI and R23K . This is in line with findings of other pediatric and adult studies, which did not detect an association of N363S and blood pressure later in life [6,24,25]. …”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, we detected an association between N363S and blood pressure; however, it disappeared in the pure carrier analysis after excluding any compound heterozygotes and carriers of BclI and R23K . This is in line with findings of other pediatric and adult studies, which did not detect an association of N363S and blood pressure later in life [6,24,25]. …”
Section: Discussionsupporting
confidence: 93%
“…A different study, although very early in life, assessing the association between GR gene SNPs with growth characteristics in neonates, did not report a significant effect of differential GR gene SNPs. 33,41 Additionally, in the current study no associations with GR gene SNPs and longterm glucocorticoid concentrations were found. This is the first study to assess the association between scalp-hair glucocorticoids and GR polymorphisms.…”
Section: Discussioncontrasting
confidence: 67%
“…GR-mediated genomic events can occur as a result of stress or GC overexposure (van den Akker et al, 2009). Previous studies have shown that polymorphisms in the coding and regulatory regions of NR3C1 are associated with the onset of some Life Sciences 91 (2012) 37-43 diseases (such as major depression, bipolar disorder, alcohol abuse, and others) and the response to GC (Bouma et al, 2011;Desrivieres et al, 2011;Manenschijn et al, 2010;. However, whether genetic variants of NR3C1 are associated with IS has not been fully researched.…”
Section: Introductionmentioning
confidence: 99%